2007
DOI: 10.1161/hypertensionaha.107.091843
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dietary Salt Enhances Sympathoexcitatory and Sympathoinhibitory Responses From the Rostral Ventrolateral Medulla

Abstract: Abstract-Increased dietary salt exaggerates arterial blood pressure (ABP) responses evoked from the rostral ventrolateral medulla (RVLM). The present study determined whether these enhanced pressor responses were directly attributable to a greater increase in sympathetic nerve activity (SNA) and whether these enhanced responses were balanced by a greater responsiveness of RVLM neurons to inhibitory input. Male Sprague-Dawley rats were fed normal chow and given access to either water or a 1% NaCl solution for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 25 publications
9
86
1
Order By: Relevance
“…62 Increasing evidence suggests that central nervous system mechanisms are involved in salt-induced hypertension, although the kidney also has a key role in salt-induced hypertension. [63][64][65][66] We sought to determine whether high salt intake increases hypertension in the SHR and whether the increased ROS production in the RVLM contributes to this mechanism. 18 High salt intake augmented the development of hypertension in the SHR beginning at the age of 6-12 weeks.…”
Section: Influence Of Salt and Obesity On Oxidative Stress In The Bramentioning
confidence: 99%
“…62 Increasing evidence suggests that central nervous system mechanisms are involved in salt-induced hypertension, although the kidney also has a key role in salt-induced hypertension. [63][64][65][66] We sought to determine whether high salt intake increases hypertension in the SHR and whether the increased ROS production in the RVLM contributes to this mechanism. 18 High salt intake augmented the development of hypertension in the SHR beginning at the age of 6-12 weeks.…”
Section: Influence Of Salt and Obesity On Oxidative Stress In The Bramentioning
confidence: 99%
“…These spinally projecting RVLM neurons are regulated by the major inhibitory and excitatory neurotransmitters GABA and glutamate, respectively (19,43). Microinjection of glutamate and glutamate receptor agonists into the RVLM results in large increases in sympathetic nerve activity and blood pressure (1, 18,39,52,60,62). Our laboratory and others have shown that sedentary vs. active rats exhibit greater indexes of sympathoexcitation when RVLM neurons are activated with glutamate (41, 50).…”
mentioning
confidence: 99%
“…At the central level, there is evidence that a high-salt diet may alter input/output signals in the medulla, including the NTS. For example, increased dietary salt was shown to alter the balance of sympathoexcitatory and sympathoinhibitory responses from/to the rostral ventrolateral medulla, while high sodium enhanced activation of neurons in the NTS and the rostral ventrolateral medulla, accounting for the observed decreased baroreflex (13,14).…”
mentioning
confidence: 99%